MEDIATING ORAL COMPETENCE THROUGH GEN-AI IN GENRE-BASED SPEAKING INSTRUCTION FOR FRACTURED NARRATIVES - Herawati, Herti; Emilia, Emi; Dewi, Finita (Universitas Islam Sumatera Utara (UISU), 2025)
Developing oral narrative skills in English as a Foreign Language (EFL) contexts is challenging. It is often made more difficult by limited opportunities for personalized feedback and the cognitive burden of real-time production. This study investigated the integration of GenAI tools, specifically Gemini and ChatGPT, within a Genre-Based Approach (GBA) to scaffold the speaking skills of 32 tenth-grade students in West Java, Indonesia. This study focuses on the creative genre of